PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN FRANCHISE O’CHICKEN DI KECAMATAN BUKITRAYA KOTA PEKANBARU - Azizah Azmi; Yusmini Yusmini; Evy Maharani (Fakultas Pertanian, Universitas Riau, 2019)
This study aims was analyze the marketing mix that influences consumer purchasing decisions O’Chicken, Analyzing the relationship between the marketing mix of consumer purchasing decisions O’Chicken. This research using purposive sampling method with the respondents of the study amounted to 50 respondents who have aged > 15 years, shop at O’Chicken more than 1 times. The data were analyzed using Likert scale, validity test, reliability test and Cartesian diagram. The results showed that of the five marketing mix variables, all of which are in the category of